2009
DOI: 10.4049/jimmunol.0801820
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-θ Is Required for NK Cell Activation and In Vivo Control of Tumor Progression

Abstract: Protein kinase C-θ (PKCθ) was initially isolated as an important PKC isoform expressed in T cells, although its expression is not restricted to these cells. Despite the central function of PKCθ in several immune responses, its role in the antitumor response against MHC class I (MHC-I)-negative cells has not been investigated. This is an important issue because most tumor cells growing in vivo down-regulate MHC-I expression to escape the CTL-mediated response. In the present work, we show that in vivo developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 50 publications
(58 reference statements)
3
52
0
Order By: Relevance
“…In the latter scenario, the presence of the complete splenocyte immune population was apparently needed, suggesting that the effect is presumably partially mediated by macrophages and/or dendritic cells. 23 Our finding is in accord with previous studies demonstrating a NK cell-dependent increase in anticancer activity of NK cells responding to poly I:C stimulation. 25 PKC-u activation in this context is presumably mediated by soluble factor(s), which could be cytokine(s) secreted by macrophages and (or) dendritic cells (DCs) that are known to activate NK cells.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…In the latter scenario, the presence of the complete splenocyte immune population was apparently needed, suggesting that the effect is presumably partially mediated by macrophages and/or dendritic cells. 23 Our finding is in accord with previous studies demonstrating a NK cell-dependent increase in anticancer activity of NK cells responding to poly I:C stimulation. 25 PKC-u activation in this context is presumably mediated by soluble factor(s), which could be cytokine(s) secreted by macrophages and (or) dendritic cells (DCs) that are known to activate NK cells.…”
Section: Introductionsupporting
confidence: 83%
“…Furthermore, in vitro testing showed that NK cells isolated from PKC-u ¡/¡ mice exhibited reduced cytotoxicity against leukemic RMA-S cells after poly-inosinic:cytidiylic acid (poly I:C) treatment ex vivo. 23 We also observed that poly I:C treatment increased the relative expression levels and the activation status of PKC-u in NK cells, both in vivo and in vitro. In the latter scenario, the presence of the complete splenocyte immune population was apparently needed, suggesting that the effect is presumably partially mediated by macrophages and/or dendritic cells.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…In NK cells, the rapid activation of PKC enables them to mediate natural cytotoxicity towards tumor cells [65,66], and PKC activation is essential for triggering lysis in IL-2-activated NK cells [6]. PKCζ was also demonstrated to be required for NK cell activation and in vivo control of tumor progression [44]. Some other report described the absolute requirement of PKCζ for ITAM-mediated IFN-γ secretion, but without a marked influence on the release of cytolytic mediators [20].…”
Section: Page 16 Of 39mentioning
confidence: 99%